(untitled) (Journal of Academic Research, 2019)
Communication is considered by many scholars as the ultimate goal of language use. For language learners to achieve such a goal, their attention should be drawn to the importance of the various communication channels within EFL classes. One of which is the so called non verbal communication which is defined as the communication through sending and receiving wordless cues (Wikipedia, the free encyclopedia). Therefore, the enclosed study which is entitled" Bridging the Gap between Students’ Teachers’ Nonverbal Communication in Libyan EFL Classes", tends to shed the light on the relationship between students’ and teachers’ non verbal communication in terms of second language use. In other words, it aims at minimizing the claimed space between teachers’ use of non verbal communication patterns and students’ receiving abilities as well as responses. To accomplish the goals of this study, which is divided into several parts including introduction, review of related literature, research method and design, results and discussions, conclusions and recommendations, 63 students of English Department, Faculty of Arts, Misurata University, Libya were handed out a questionnaire to figure out the effect of spanning the break between teachers’ students’ non verbal form of interaction.